Preparation and characteristics of the sulfonated chitosan derivatives electrodeposited onto 316l stainless steel surface - Huang, Ye (2018)
In order to ameliorate the properties of corrosion resistance and achieve applications in anti-biofouling of 316L stainless steel (SS), a sulfated derivative of chitosan was deposited onto stainless steel surface by an electrochemical method. In detail, chitosan-catechol (CS-CT) was synthesised in the hydrochloric acid solution by the Mannich reaction and then electrodeposited on the surface of the polished 316L stainless steel. The chitosan-catechol deposited SS sample was further modified with maleic anhydride and sulfite. The grafting progress was monitored by FTIR, UV spectrophotometer and X-ray photoelectron spectroscopy. Hydrophilicity and corrosion resistance of modified SS were characterized by water contact angle measurements, Tafel curves and electrochemical impedance spectroscopy. The morphology of the SS surface before and after the modification was investigated by atomic force microscopy and scanning electron microscope. Further, the anti-biofouling performance in terms of the anti-adsorption protein and anti-bacteria effects of all modified SS samples were estimated, and the modified 316L exhibits the capability of lower protein adsorption and improved antibacterial effect.